Regionalização de vazões mínimas de referência Q7,10 e Q90 - Ferreira, Gláucia Machado (2010)
The main objective of the research was the study and application of different methods for estimating ten years return period minimum annual seven consecutive days low flows (Q7,10) and minimum flows associated with remaining 90% in time (Q90), for the region between Doce and Itabapoana basins, through the hydrological regionalization. The three compared methods are: Eletrobrás (1985a), Eletrobrás (1985b) and Chaves et al. (2002). The physical characteristics used in the regionalization by the Eletrobrás (1985a) method were drainage area (A), length of the main river (L), watershed drainage s density (Dd), watershed medium slope (Sm) and main river slope (SL), extracted from a hydrological consistent elevation model (HCDEM). Climatic characteristic was represented by average annual rainfall (P). Q7,10 values were estimated by fitting three parameter Log-Normal probability distribution. Q90 values were obtained from daily permanence curve for each water discharge gaging station. Regression equations were estimated for two hydrographic regions. Additional analyses was made for the Itapemirim watershed. Results were compared, taking into consideration determining coefficients, factorial standard deviations and results of F-tests. By the methods Chaves et al. (2002) and Eletrobrás (1985b), the discharges were estimated by the applying different equations, depending on the relative location of the discharge gaging stations. Results obtained by the different methods were compared with those from previous studies developed for the study region by using two indexes: percentual error average and Nash and Sutcliffes s efficiency coefficient. The results indicated that the digital elevation model obtained for the study area was hydrologically consistent and allowed automatic estimation of basin physical characteristics. Drainage area, length of the main river and watershed medium slope were the variables that best represented Q7,10 and Q90 in the Eletrobrás (1985a) regionalization method. The Eletrobrás (1985a), based on regional regression equations, allowed the obtaining of the best fitting equations to the Q7,10 and Q90 variables